Case Report: Empyema secondary to percutaneous transthoracic needle biopsy in three cases - Du, Rao; Mao, Hui; Li, Wei Min; Liu, Dan; Wang, Kaige (Frontiers in Medicine, 2025)
Percutaneous transthoracic needle biopsy (PTNB) is a widely utilized diagnostic procedure for pulmonary lesions, with the current literature predominantly documenting pneumothorax and hemorrhage as primary complications. While empyema represents a rare complication, its clinical implications warrant special attention. In this study, we report the cases of three patients with unidentified pulmonary masses who developed empyema after PTNB. All cases exhibited fever (24–48 h post-procedure) and radiographic evidence of pleural effusion progression shortly after the procedure, which was successfully managed through pleural drainage and antibiotic treatment. These findings suggest that pre-procedural infectious foci may be prone to iatrogenic pleural seeding during PTNB. This report emphasizes the necessity of monitoring infectious indicators in patients undergoing biopsy of cavitary or necrotic lesions. Physicians should exercise caution when puncturing lumps suspected of abscesses and remain vigilant for empyema secondary to PTNB if the patient shows signs of infection.